Pandangan Hukum Islam Terhadap Investasi - Ayu Oktavia; Vira Septiani; Rohanah Rohanah; Nabila Nabila; Yayat Suharyat (LPPM Politeknik Pratama, 2023)
The aim is to explain the concept and principle of investment against the view of Islamic law. In Islamic law, investment is seen as an investment activity to earn income. However, sharia principles prohibit the use of riba or interest-based loans. Islam encourages people to engage in productive activities by investing in their businesses. This research method is carried out through the discovery of indirectly finding data sourced from various sources or references. On the other hand, technical input discussions are carried out using leaving conclusions. The results of this examination illustrate that the existence of the sharia asset market in Indonesia is an important part in giving up long-term funding flexibility for money owners. This stands from the increase in value of Islamic money owners every year. The market value of parts of Indonesia and the Sharia Stock Index is also creeping age meaningfully sourced day by day. This shows that the Islamic asset market holds intelligence to move the national economy. Investing in the Islamic asset market can be oriented near a fairer incentive money supply and strengthen the happy incentive money to bypass taxes. This study also shows that the Islamic asset market is compatible with the passion of money owners who hold religious ideals to allow their investment to be compatible with sharia beliefs. In funding, sharia ethics on what is permissible, what is prohibited, and the effects that are similar to integrated fragments are sourced from funding designs.